The Structural Basis of the Disabling of the Actin Polymerization Machinery by Yersinia - Lee, W (2013)
Yersinia pestis is a human pathogen and the causative agent of bubonic plague, responsible for causing three massive pandemics, resulting in hundreds of millions of deaths in the 14th century alone. Yersinia’s virulence stems from its ability to overcome host immune defences by the injection of six Yersinia outer proteins (Yops) into the host cells via its Type III secretion system. One of these Yops, YopO specifically disables the actin polymerization machinery, leading to the crippling of phagocytosis. YopO consists of a GDI domain which sequesters Rac and Rho, and a kinase domain, the activity of which is dependent on host actin. Little is known about the targets of the kinase domain and the mechanism of function of YopO remains incomplete. In this work, YopO was crystallized in complex with actin, revealing that YopO binds to actin on subdomain 4, away from the 'hotspot’ between subdomains 1 and 3 which is involved in binding most actin-binding proteins. The structure reveals how recruitment of YopO-bound actin monomers stalls actin polymerization by steric hindrance. The structure also demonstrates how YopO uses actin for self-activation and suggests that actin is being used by YopO as bait for recruitment into actin machineries. Using SILAC mass spectrometry, actin cytoskeletal machineries within macrophages that recruit YopO are identified and these include, amongst others: VASP family proteins, gelsolin family proteins, formins and WASP. Of these, VASP, EVL, diaphanous1, WASP and gelsolin have been identified to be phosphorylated by YopO and were validated by in vitro phosphorylation. This work demonstrates that YopO uses actin as a scaffold for selection of kinase substrates, enabling targeted phosphorylation of the actin machinery and provides insight into the regulation of the actin cytoskeleton by phosphorylation under non-pathogenic conditions.